Plutarch's Life of Alcibiades : Story, Text and Moralism - Verdegem, Simon (Book collections on Project MUSE., 2010)
At the beginning of the second century AD, Plutarch of Chaeronea wrote a series of pairs of biographies of Greek and Roman statesmen. Their purpose is moral: the reader is invited to reflect on important ethical issues and to use the example of these great men from the past to improve his or her own conduct. This book offers the first full-scale commentary on the Life of Alcibiades. It examines how Plutarch's biography of one of classical Athens' most controversial politicians functions within the moral programme of the Parallel Lives. Built upon the narratological distinction between story an.